Hacia la comprensión de la naturaleza transnacional de las audiencias televisivas: Imaginarios, desterritorialización, hibridación, globalización (2015)
This text proposes a second thought to television audiencetransnational nature assuming that this exceeds a specificcircumstance of migrants and that due to economy globalizationof communication it installs on the nature of communicationprocesses. In the first part, .a conceptualization of what istransnational applied to audiences will be proposed, and inthe second part, the argument that this transnational characterhas been originated in the development and massification ofdigital technology and the processes of economy globalizationwhich have allowed the consolidation of media translationalcorporations is developed. In this sense, transnationality ofaudiences exceeds specific circumstances linked to migrationsand is installed on the nature of communication developed insociety